DAMPAK PACARAN SECARA HOLISTIK TERHADAP REMAJA - Hikmah, Hikmah; Ayu Utami, Arifah Sekar; Sholikah, Iis (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
This study aims at knowing the impact of going to the physical, psychological, social, spiritual (holistic ) in class X and XI in MAN 1 Wates in 2013. The reason this research because the results obtained from indepth interviews in 4 students MAN 1 Wates lack of knowledge about the courtship activities and impact so there are irregularities in the reproductive organs as well as the impact of physical, psychological,social and spiritual students. The method used by the Qualitative Quantitative Descriptive sampling technique used